Interventions to address the mental health of adolescents and young adults living with or affected by HIV: state of the evidence. (24th June 2021) - Bhana, Arvin; Kreniske, Philip; Pather, Ariana; Abas, Melanie Amna; Mellins, Claude A
Abstract: Introduction: Adolescents and young adults (AYA) remain vulnerable to HIV‐infection and significant co‐morbid mental health challenges that are barriers to treatment and prevention efforts. Globally millions of AYA are living with HIV (AYALH) and/or have been affected by HIV in their families (AYAAH), with studies highlighting the need for mental health programmes. With no current guidelines for delivering mental health interventions for AYALH or AYAAH, a scoping review was undertaken to explore current evidence‐based mental health interventions for AYALH and AYAAH to inform future work. Methods: The review, targeting work between 2014 and 2020, initially included studies of evidence‐based mental health interventions for AYALH and AYAAH, ages 10 to 24 years, that used traditional mental health treatments. Given the few studies identified, we expanded our search to include psychosocial interventions that had mental health study outcomes. Results and discussion: We identified 13 studies, seven focused on AYALH, five on AYAAH, and one on both. Most studies took place in sub‐Saharan Africa. Depression was targeted in eight studies with the remainder focused on a range of emotional and behavioural symptoms. Few studies used evidence‐based approaches such as Cognitive Behaviour Therapy; psychosocial approaches included mental health treatments, group‐based and family strengthening interventions, economic empowerment combined with family strengthening, group‐based mindfulness and community interventions. Eleven studies were randomized control trials with four pilot studies. There was variation in sample size, treatment delivery mode (individual focus, group‐based, family focus), and measures of effectiveness across studies. Most used trained lay counsellors as facilitators, with few using trained mental health professionals. Eleven studies reported positive intervention effects on mental health. Conclusions: Despite the need for mental health interventions for AYALH and AYAAH, we know surprisingly little about mental health treatment for this vulnerable population. There are some promising approaches, but more work is needed to identify evidence‐based approaches and corresponding mechanisms of change. Given limited resources, integrating mental health treatment into healthcare settings and using digital health approaches may support more standardized and scalable treatments. Greater emphasis on implementation science frameworks is needed to create sustainable mental health treatment for AYALH and AYAAH globally.